Sistema Ambiental Estratégico, modelo para la competitividad territorial. Caso: Bajo Urubamba - Cacho Cruz, Rocío (2013)
The objective of this paper is to show the Strategic Environmental System (SAE) as a tool to strategic planning, and a model to territorial competitivity applied in practice with long run objectives to integrate the environmental aspects in the development planning processes, increasing the knowledge level about the environmental context and the interrelations with other dimensions of sustainable development.